Structured and unstructured physical activity habits: a study on adolescents’ motivational characteristics for exercising - Armando Cocca; Michaela Cocca; Klaus Greier; Gerhard Ruedl (International Journal of Adolescence and Youth)
Structured (sports club, SC) and unstructured (leisure-time exercise, LTE) physical activities (PAs) are key for the enhancement of health in adolescents, motivation being a potential factor of adolescents’ active habits. The aim of this study was to analyse the motivational characteristics of different PA profiles based on adolescents’ engagement in SC-PA and LTE-PA. Cluster analyses on a sample of 1332 participants (14.27 ± 2.18 years old) highlighted low-PA (SC + LTE >10 hours/week) and high-PA profiles (n = 536, mean of 5.41 hours/week SC PA and 5.42 hours/week LTE) for the overall sample and those who identified themselves as female. The male-gender sub-sample clustered in six PA profiles. Motivational characteristics were similar across profiles, with high autonomous and low controlled motivation regardless of the total weekly PA. SC-based PA was the strongest contributor to overall PA and should be promoted to increase adherence to exercise.